Penerapan Multimedia Dalam Meningkatan Keterampilan Menulis Teks Deskripsi Siswa Kelas VII SMPN 18 Makassar - Oddang, Andi Tenri; Wijayanti, Tuti; Mangile, Nisma (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to describe the application of multimedia in improving the writing skills of descriptive texts of seventh grade students of SMPN 18 Makassar. The research used Classroom Action Research method. The research subjects were the seventh grade students of SMPN 18 Makassar, totalling 32 students. The research data were analysed qualitatively and quantitatively to measure the effectiveness of the application of multimedia in improving students' writing skills. Qualitative analysis was used to understand the learning process and students' responses, while quantitative analysis was used to evaluate the improvement of students' learning outcomes through the comparison of scores between cycles. The results showed a significant improvement in students' description text writing skills from the first cycle to the second cycle. This improvement shows that the use of multimedia is effective in improving students' description text writing skills. Based on the results of the study, the use of multimedia is recommended to be widely applied in writing learning at junior high school level.